Preparation of bulk metallic glasses by modifying local structure of icosahedral quasicrystals. (June 2019) - Li, Zijing; Pan, Shaopeng; Zhang, Suhong; Feng, Shidong; Li, Maozhi; Liu, Riping; Tian, Yongjun; Wang, Li-min
Abstract: An attempt is carried out to design metallic glasses by modifying the local structure of icosahedral quasicrystals. A series of metallic glasses are prepared by introducing beryllium to the quasicrystal former, Zr40 Ti40 Ni20, and the maximum diameter of the glasses reaches 20 mm. A phase transformation diagram is constructed for the alloys of (Zr40 Ti40 Ni20 )100-x Bex, revealing the transition from stable crystal to quasicrystal and then to metallic glasses with the increased Be content. This study shows a connection between the formation of metallic glasses and the specific thermodynamics of the initially precipitated quasicrystals. Interestingly, both improvements in the forming ability for glasses and quasicrystals are observed over a wide composition range. Ab initio molecular dynamic simulations show the evolution of the structural features of the metallic melts for the optimised glass forming region, which guarantee the primary precipitation of quasicrystal. Highlights: A new method to design metallic glasses is proposed via the typical quasi-crystal. The study offeres a model system for the study of the connection between metallic glasses and icosahedral quasi-crystals. The connection between metallic glasses and quasi-crystals is clarified, and the traditional arguments is revised.